(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The integration of culture into English language teaching has become one of the most important priorities of contemporary education. Modern language teaching aims not only to develop linguistic competence but also to foster intercultural communicative competence, enabling learners to communicate effectively in multicultural environments. One of the most effective methods for achieving this goal is the use of realia, authentic objects and materials representing everyday life and cultural heritage. This article explores the pedagogical potential of Uzbek national cultural realia in English language classrooms. Drawing on the theories of intercultural communicative competence, sociocultural learning, culturally responsive teaching, and authentic materials development, the study examines how traditional clothing, cuisine, historical monuments, handicrafts, and cultural celebrations can be used to enhance language learning. The findings suggest that realia-based instruction contributes to vocabulary acquisition, speaking proficiency, learner motivation, cultural awareness, and intercultural understanding. Furthermore, it enables learners to represent their national identity confidently in international communication. The article concludes that integrating Uzbek cultural heritage into English language teaching promotes both language development and cultural preservation.